Microcontroller based three-level zero voltage switching pulse-width-modulation DC-to-DC converter - Shakina, Abu Hasan (2008)
The purpose of this project is to develop a Three-Level Zero Voltage Switching PWM DC-to-DC Converter controlled by Microcontroller. The scopes of works for this project include to convert DC to DC voltage, implement Zero Voltage Switching (ZVS) to increase the efficiency and lastly to apply the Microcontroller for switching. A zero-voltage-switching pulse-width-modulation three-level (ZVS PWM TL) converter realizes ZVS for the switches with the use of the leakage inductance (or external resonant inductance) and the output capacitors of the switches, however, the rectifier diodes suffer from reverse recovery which results in oscillation and voltage spike. In order to solve this problem, this paper proposes a novel ZVS PWM TL converter, which introduces two clamping diodes to the basic TL converter to eliminate the oscillation and clamp the rectified voltage to the reflected input voltage; microcontroller will generates PWM in order to operate MOSFETs so that the converter can be turn on. Meanwhile, all the switches keep realizing ZVS.